Indocyanine green fluorescence imaging in hepatobiliary surgery - Majlesara, Ali; Golriz, Mohammad; Hafezi, Mohammadreza; Saffari, Arash; Maier-Hein, Lena; Müller, Beat P.; Mehrabi, Arianeb (Photodiagnosis and photodynamic therapy, 2017)
Indocyanine green (ICG) is a fluorescent dye that has been widely used for fluorescence imaging during hepatobiliary surgery. ICG is injected intravenously, selectively taken up by the liver, and then secreted into the bile. The catabolism and fluorescence properties of ICG permit a wide range of visualization methods in hepatobiliary surgery. We have characterized the applications of ICG during hepatobiliary surgery into: 1) liver mapping, 2) cholangiography, 3) tumor visualization, and 4) partial liver graft evaluation. In this literature review, we summarize the current understanding of ICG use during hepatobiliary surgery. Intra-operative ICG fluorescence imaging is a safe, simple, and feasible method that improves the visualization of hepatobiliary anatomy and liver tumors. Intravenous administration of ICG is not toxic and avoids the drawbacks of conventional imaging. In addition, it reduces post-operative complications without any known side effects. ICG fluorescence imaging provides a safe and reliable contrast for extra-hepatic cholangiography when detecting intra-hepatic bile leakage following liver resection. In addition, liver tumors can be visualized and well-differentiated hepatocellular carcinoma tumors can be accurately identified. Moreover, vascular reconstruction and outflow can be evaluated following partial liver transplantation. However, since tissue penetration is limited to 5-10mm, deeper tissue cannot be visualized using this method. Many instances of false positive or negative results have been reported, therefore further characterization is required.